Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Prove taht the following inequality holds $$a^ab^bc^c\ge (abc)^{\frac{a+b+c}3}$$ if $a,b,c$ are positive.

I'm not sure how to handle these kinds of powers. Are there any "famous" but not so advanced inequalities that involve this kinds of expressions?

I was trying to do something like ordering them without lost of generality because it's symmetric, but I get nowhere and I just make the thing even more complicated.

I'm asking for solution rather than hints since this is my first time encountering these kinds of problems.

share|improve this question
add comment

3 Answers

up vote 5 down vote accepted

Take logarithms. The function $x\log x$ is convex. The result now follows from Jensen's Inequality (use "weights" $1, 1, 1$).

share|improve this answer
add comment

Take the logs to get rid of the powers ;)

$$a \ln(a) + b \ln (b) + c \ln (c) \geq \frac{a+b+c}{3} [ \ln (a)+ \ln(b) + \ln(c)] $$

Then a relatively simple but less known inequality,Chebyshev Inequality , solves the problem.

If you are not familiar to chebashev, try proving directly that

$$a \ln(a) + b \ln (b) \geq a \ln(b) + b \ln(a) $$

Do the same for $(a,c), (b,c)$ and add them togeter....

P.S. The last observation leads to the following "elementary" but more complicated solution.

We prove first that

$$a^ab^b \geq a^bb^a \,.$$

Indeed since the equation is symmetric, we can assume WLOG that $a \geq b$ and then

$$a^{a-b} \geq b^{a-b} \,.$$

Which is exactly the desired inequality.

Then we have

$$a^ab^b \geq a^bb^a \,.$$ $$a^ac^c \geq a^cc^a \,.$$ $$b^bc^c \geq b^cc^b \,.$$ $$a^ab^bc^c \geq a^ab^bc^c \,.$$

Multiplying togeter, you get

$$a^{3a}b^{3b}c^{3c} \geq (abc)^{a+b+c} \,.$$

What I did here was to reprove the Chebashev inequality in this particular case, without writing the logs....

share|improve this answer
add comment

This might be a bit similar to N.S.'s answer but here goes anyway:

Take logarithms. Without loss of generality, take $a\leq b\leq c$. Define:

$x_1 = x_2 = x_3 = \frac a3, \\x_4 = x_5 = x_6 = \frac b3, \\x_7 = x_8 = x_9 = \frac c3, \\y_1 = y_2 = y_3 = \log a, \\y_4 = y_5 = y_6 = \log b, \\y_7 = y_8 = y_9 = \log c.$

Clearly, $x_1 \leq x_2 \leq \cdots \leq x_9$ and $y_1 \leq y_2 \leq \cdots \leq y_9$.

Now just use the rearrangement inequality on this and you're done.

share|improve this answer
add comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.